Nudging- en knuff i rätt riktning till hållbar bostadsområden - Arvidsson, Linnea; Citess, Malin; Johansson, Emma; Larsson, Sanne; Ossiansson, Filip; Åström, Elin (My University, 2019)
The world is constantly changing and sustainable development will be the guiding expression in the transformation and to fulfill the needs of current generations and those to come. Everyone is responsible and the construction industry is no exception. In order to achieve "Sustainable Cities and Societies", a part of "Agenda 2030", one must look at the entire life cycle of the building and the behaviour of the residents. Clever solutions that environmentally, economically and socially benefit both community development and future generations are key to success. Nudging is an expression introduced in 2008 by the behavioral economist and Nobel prize laureate, Richard H. Thaler. By facilitating a decision processes, one can nudge people to desirable decisions without restricting the freedom of choice. The use of nudging as a method is growing rapidly in various industries and the construction industry has recently embarked the method to improve the sustainability. Wästbygg is a construction company that tries to create a concept for future projects by using nudging and t he company has named its investment to Boaktiva. The purpose of the project is to give an introduction to nudging and examine how the method can be used in the construction industry with a focus on the design of residential areas. By evaluating an existing investment and considering new ideas, the project creates an opportunity for Wästbygg as well as other companies to draw lessons for future development of housing projects. The project is based on a comprehensive literature review followed by two surveys; one to the residents of Wästbyggs project Frösundavik and one to the public. Interviews were held with several involved organisations and companies in order to gain a better understanding of the benefits and improvements of Boaktiva. There are many different ways to use nudging in housing projects to create more socially and ecologically sustainable residential areas. Several different tools to nudge were implemented in Frösundavik with varying levels of success. The results show positive effect of implemented tools but also a need of further development. The lessons learned from the study are presented in form of a checklist with recommendations for successful nudging when designing residential areas. A conclusion is that design and development of sustainable residential areas can benefit from nudging. The method would profit from more trials and careful evaluation of tested examples. If knowledge from inventive projects gets successfully transferred within and between companies, big differences can be made by simple solutions.